Morphological features of chronic virus-associated gastritis and duodenitis - S. Yu. Yermak; S. A. Lyalikov; M. G. Zubritsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate the prevalence rate of Herpes simplex virus type 1 and 2 (HSV-1 and HSV-2), Epstein-Barr virus (EBV), human papillomavirus (HPV), cytomegalovirus (CMV) and Helicobacter pylori (H. pylori) in the stomach and duodenal mucosa of patients with chronic gastritis and chronic duodenitis of different age, and to analyze the correlation between morphological scores and pattern of mucosa infection. Material and methods. The original study included 116 patients (66 children and 50 adults) with the verified chronic gastritis and chronic gastroduodenitis. All patients underwent upper endoscopy with biopsy of the stomach and duodenal mucosa. Biopsy samples were processed by the standard technique with hematoxyline and eosine staining of sections. The basic morphological features were estimated by semiquan titative method according to modified Sydney system. Helicobacter pylori infection was diagnosed by histological method i.e.: Romanovsky-Gimza stain of biopsy samples. HSV-1, HSV-2, EBV, CMV and HPV antigens were determined by streptavidin-biotin method in paraffin sections. Results. Pathological scores of the stomach and duodenal mucosa are related to the pattern of infection in children and adults. Conclusions. Virus antigens were found in 57% of the studied children and 64% of adults in stomach and duodenal mucosa. Presence of HSV-1 infection alters of the severity and activity of chronic inflammation in stomach mucosa in children and adults.